Manejo nutricional na qualidade da cana-de-açúcar e produção de etanol em final de safra - Gambarini, Eduardo Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Sugarcane is one of the main crops grown in Brazil, being very predominant in the Central-South geoeconomic region, where around 90% of its national production is concentrated. This region has a characteristic climate with low rainfall during the winter, which can cause great losses in the sugarcane fields and, consequently, in the industry. The use of a complementary management program during the dry season can favor a good performance of the plant even in periods of stress, ensuring that the quality of the raw material does not suffer great damage. In this context, the objective of this study was to evaluate the effects of the incorporation of nutritional management via the leaves in autumn, associated or not with boron, on the quality of sugarcane stalks and on the production of ethanol. The design was carried out in randomized blocks with 5 replications. The treatments consisted of the Control, 6 L.ha-1 of the Nutritional Complex (1% N; 6% P2O5; 6% K2O; 2% Mg; 2.5% of S and 1.6% of amino acids), 6 L.ha-1 of the Nutritional Complex associated with 2 L.ha-1 of Boron. Technological analyzes of the extracted juice, clarified juice and wine were carried out; and microbiological analysis at the beginning and end of the fermentation process. The use of 6 L.ha-1 of Nutritional Complex associated with 2 L.ha-1 of Boron (10% boric acid), provided lower concentration of Total Residual Reducing Sugars (TRRS) in wine and higher Alcohol Content and Fermentation Efficiency in relation to the other treatments tested.

A cana-de-açúcar é uma das principais culturas cultivadas no Brasil, sendo muito predominante na região geoeconômica Centro-Sul, onde se concentra cerca de 90% de sua produção nacional. Esta região possui clima característico com baixa pluviosidade durante o inverno, o que pode ocasionar grandes perdas nos canaviais, e, consequentemente, na indústria. A utilização de um programa de manejo complementar na época da pré-seca pode favorecer um bom desempenho da planta mesmo em períodos de estresse, garantindo que a qualidade da matéria-prima não sofra grandes danos. Neste contexto, o objetivo do trabalho foi avaliar os reflexos da incorporação de um manejo nutricional via foliar no outono, associado ou não ao Boro, na qualidade dos colmos de cana-de-açúcar e na produção de etanol. O delineamento foi realizado em blocos casualizados com 5 repetições. Os tratamentos foram constituídos por Controle, 6 L.ha-1 do Complexo Nutricional (1% de N; 6% de P2O5; 6% de K2O; 2% de Mg; 2,5% de S e 1,6% de aminoácidos), 6 L.ha-1 de Complexo Nutricional associado à 2 L.ha-1 de Boro (ácido bórico à 10%). Foram realizadas análises tecnológicas do caldo extraído, caldo clarificado e vinho; e análises microbiológicas no início e final do processo fermentativo. O uso de 6 L.ha-1 de Complexo Nutricional associado à 2 L.ha-1 de Boro, proporcionou menor concentração de Açúcares Redutores Residuais Totais (ARRT) no vinho e maior Teor Alcoólico e Eficiência Fermentativa em relação aos demais tratamentos testados.
Nutritional management in sugarcane quality and ethanol production at the end of the harvest
Keywords: Plantas Nutrição; Fermentação; Etanol; Cana-de-açúcar; Plantas Efeito do boro